REIS, Daniel Aarão. Ditadura e democracia no Brasil: do golpe de 1964 à Constituição de 1988. Rio de Janeiro: Zahar, 2014 - Martins de Souza, César Augusto (Revista Territórios e Fronteiras, 2015)
Resenha da obra.